Cervical length mid trimester in low risk women fails to predict the majority of pre term births. (7th June 2011) - Kenyon, A; Braschi, J; Forya, F; Peebles, D; David, A
Abstract : Introduction: Pre term birth (PTB) is a leading course of morbidity and mortality. Prediction is possible but lacks sensitivity. Mid trimester ultrasound of cervical length (MCL) can identify women at high risk of PTB in the general population, there is little data on the risk in low risk (LR) populations. Methods: All women attending for antenatal care at our institution between 1 January 2009 and 30 June 2010 underwent MCL screening. Data on PTB risk factors was routinely collected; outcome was recorded. LR women with MCL<15 mm were all managed in a specialist clinic according to best evidence. Results: Of 6511 women undergoing MCL at 18–25 weeks (wks) gestation, 352 (5%) had risk factors for PTB: cervical surgery (n=147), previous PTB <37 wks of gestation (n=200), mid trimester spontaneous abortion (n=7) or uterine anomaly (n=18) (table 1 ). There were 140/6511 spontaneous PTB (<37). Of LR women (125) only 14% (17) and 5% (6) had MCL ≤25 & ≤15 mm respectively. For those LR women delivering <28 wks gestation (13/15) 46% (6/13) and 15% (2/13) had MCL ≤25 and ≤15 mm respectively. Conclusion: A MCL >15 mm in a LR woman carries a LR of PTB, however a short cervix mid trimester fails to identify 86% of LR women who will subsequently deliver pre term. A better screening test for PTB is needed in women of LR to better direct antenatal care.